From the gift to the gospel of life: for a theological interpretation of the Encyclical Evangelium Vitae. - Carrasco de Paula, Ignazio (Medicina e Morale, 1995)
After briefly comparing the Encyclical Evangelium Vitae (EV) with the Instruction of the Congregation for the Doctrine of Faith Donum Vitae, the article indentifies two reasons for the pontificai decision to repropose a new document on the protection of life. First of all the creeping retum of euthanasia, a problem which is strictly connected to medicai ethics. The second reason is more complex and is rooted in today's social-cultural context, which is characterized by systematic and aggressive behaviour against life in its "weakest" expressions (like the embryo or thc terminally sick). And moreover, what many people feel is that the criminal characteristic of this kind of behaviour has been lost, to the point where legal legitimacy is even being requested as a right. This is exactly why the EV transcends the doctrinal context which is typical of the pontificai documents on bioethics in arder to acquire the depth and broadness of vision which are characteristic of the great social encyclicals. In fact, according to the author, it is no longer just a question of offering an ethical opinion on specific problems but rather of mobilizing moral and spiritual resources which lead to a social and cultural recovery of the centrality of the human person and of his dignity. Moving from these premises, the author reflects on the EV from a theological point of view, discussing the three basic principles of the Encyclical: the immorality of the direct and voluntary killing of an innocent human being; direct abortion as a serious moral disorder; euthanasia as a serious violation of the divine law.